Fabrication of a novel nanocomposite Ag/graphene@SiO2–NaLuF4:Yb, Gd, Er for large enhancement upconversion luminescence1. Issue 24 (28th June 2015) - Yin, Dongguang; Cao, Xianzhang; Zhang, Lu; Tang, Jingxiu; Huang, Wenfeng; Han, Yanlin; Wu, Minghong
<x xml:space="preserve">Abstract</x> Upconversion nanocrystals have a lot of advantages over other fluorescent materials.